A prospective evaluation of lung function at three and six months in patients with previous SARS-COV-2 pneumonia. (September 2021) - Orzes, Nicla; Pini, Laura; Levi, Guido; Uccelli, Silvia; Cettolo, Francesca; Tantucci, Claudio
Abstract: Objective: This study investigated the consequences of Coronavirus Disease 2019 (COVID-19) pneumonia on lung function in the first 6 months after hospital discharge. Methods: A prospective lung function assessment in SARS-CoV2 patients with COVID-19 pneumonia, hospitalized between March and April 2020, was conducted with spirometry measurements including lung volumes, mainly total lung capacity (TLC), lung diffusion capacity for carbon monoxide (DLCO ) collected at 3 months after hospital discharge. Patients with restrictive ventilatory defect or impaired DLCO or both were re-evaluated at 6 months with global spirometry and chest HRCT scan. Results: Among 40 consecutive patients, 19 (48%) had normal pulmonary functional tests (group A), and 21 (52%) showed residual lung function abnormalities at 3 months after hospital discharge (group B). In group B, 4 patients (19%) had only loss of lung volume as shown by TLC reduction (group 1), 13 patients (62%) had decreased both TLC and DLCO (group 2), and 4 patients (19%) had isolated reduction in DLCO (group 3). At 6-month follow-up in group 1, although all patients improved, only one normalized total lung capacity (TLC). In group 2, TLC and DLCO increased significantly (p < 0.01), but only 3 patients reached normal values. In group 3, DLCO improved for most patients, normalizing in 50% of them. At 6-months significant correlations between an internal-built chest HRCT scan severity score and TLC (r 2 = 0.33; p < 0.01) and DLCO (r 2 = 0.32; p < 0.01) were found. Conclusions: Nearly 50% of patients recovered in the post-critical phase. Most of those with abnormal pulmonary function tests at 3 months improved subsequently, but only another 29% (6 out of 21) reached normal values at 6 months. These results indicate that lung function spontaneous recovery is faster at first and occurs more slowly thereafter, leaving more than one third (15 out of 40) of patients with abnormal lung function tests at 6 months. Highlights: After COVID-19 pneumonia, nearly 50% of patients fully recovered lung function. Most of those with abnormal pulmonary function tests at 3 months improved later. However, only another 29% reached normal values at 6 months. Lung function recovery is faster at first and occurs more slowly thereafter. More than one-third of patients keep abnormal lung function tests at 6 months.